2021
DOI: 10.1002/ptr.7182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of purslane supplementation on C‐reactive protein levels and biomarkers of oxidative stress as marks for metabolic syndrome: A systematic review and meta‐analysis of randomized controlled trials

Abstract: The antioxidant and antiinflammatory properties of purslane (Portulaca oleracea L.) are known in preclinical studies but further examination is needed to expand their potential into the clinical scenario. A systematic review and meta-analysis of randomized controlled trials were performed to elucidate the effects of purslane supplementation on C-reactive protein (CRP) levels and biomarkers of oxidative stress in metabolic syndrome, its related complications, and other diseases. PubMed/ MEDLINE, Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(83 reference statements)
0
4
1
Order By: Relevance
“…Moreover, a large number of studies have revealed that purslane has a high omega‐3 fatty acids content, which has been associated with lowering MDA and TAC (Abdollahzad et al, 2009 ; Badgujar et al, 2015 ; Boonthongkaew et al, 2021 ; Grabež et al, 2022 ). As opposed to our finding, a meta‐analysis and systematic review of 10 intervention trials showed insignificant effect of purslane supplementation on MDA, TAC (Zhu et al, 2021 ). In vitro studies on purslane's anti‐oxidant mechanisms suggested that the extract could reduce oxidative stress by altering the blood and liver antioxidant enzyme activities, which would result in higher levels of leptin/−actin and liver peroxisome proliferator‐activated receptors (PPAR) a/−actin (Chen et al, 2012 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, a large number of studies have revealed that purslane has a high omega‐3 fatty acids content, which has been associated with lowering MDA and TAC (Abdollahzad et al, 2009 ; Badgujar et al, 2015 ; Boonthongkaew et al, 2021 ; Grabež et al, 2022 ). As opposed to our finding, a meta‐analysis and systematic review of 10 intervention trials showed insignificant effect of purslane supplementation on MDA, TAC (Zhu et al, 2021 ). In vitro studies on purslane's anti‐oxidant mechanisms suggested that the extract could reduce oxidative stress by altering the blood and liver antioxidant enzyme activities, which would result in higher levels of leptin/−actin and liver peroxisome proliferator‐activated receptors (PPAR) a/−actin (Chen et al, 2012 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Increased levels of inflammatory biomarkers in patients with NAFLD might affect the pathogenesis of cardiovascular diseases. CRP is a protein produced by the liver under stimulation of pro-inflammatory cytokines, and the hs-CRP assay is a recommended marker of low-grade inflammation for screening the risk of cardiovascular diseases ( 48 50 ). It is no wonder that hs-CRP is a non-invasive complementary marker of NAFLD, and its high levels are common in this population due to the interplay between fatty liver and cardiometabolic problems ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Purslane has been associated with plausible mechanisms that have antiobesity efects. Given the signifcant roles of oxidative stress and infammation in the development and progression of obesity, the potential protective efects of purslane against obesity and its related complications could be attributed to its antioxidant and anti-infammatory properties [18,46]. Te previous literature has also suggested that purslane can positively impact insulin resistance [47], leading to potential improvements in weight management [48].…”
Section: Discussionmentioning
confidence: 99%
“…It has been traditionally used to treat many diseases due to its antiinfammatory and antioxidant properties [16] and its active biologic compounds that are benefcial to human health [17]. Purslane's most active compounds include omega-3, tocopherol, carotene, amino acids, thiamine, ascorbic acid, niacin, and phenolic compounds such as quercetin, kaempferol, cafeic acid, ferulic acid, and p-coumaric acid [18]. Purslane has the highest concentration of omega-3 fatty acids, particularly alpha-linolenic acid, when compared to other leafy green vegetables [19].…”
Section: Introductionmentioning
confidence: 99%